Determination of Optimum Temperature for Amount Lactic Acid Bacteria and Antioxidant Activity from Pickled Bamboo Betung Boobs (Dendrocalamus asper) - Pasaribu, Nurul Alda; Manalu, Kartika; Nasution, Rizki Amelia (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2024)
Pickled betung bamboo shoots (Dendrocalamus asper) are a traditionally fermented product and can potentially be a source of probiotics. Pickled bamboo shoots contain good microorganisms, namely LAB, which are bacteria that contribute to the food sector for natural fermentation. Fermentation of bamboo shoots produces antioxidant compounds at an optimum temperature range. The research aims to understand the optimum temperature for the amount of LAB and antioxidant activity in pickled betung bamboo shoots. This research is a laboratory experiment with 3 treatments, namely 100 grams of bamboo shoots fermented with pickled bamboo shoots at a temperature of 15℃ (K1), a temperature of 37℃ (K2), and a temperature of 40℃ (K3). The three treatments were incubated for 72 hours with 4 repetitions. The research stages included processing pickled bamboo shoots, isolating bacteria using the dilution series-pour plate method, and antioxidant testing using the DPPH method. The number of LAB is calculated using the Quebec Colony Counter. Data analysis used Anova and Duncan's test. The results obtained include that temperature influences the amount of BAL in pickled bamboo shoots with a value of p=0.016. The number of LAB at a temperature of 150C was 59.50, at a temperature of 37 129.74, and a temperature of 40 107.57. Temperature also affects antioxidant activity. The average values at temperatures of 15.37, 40℃ are 30.60%, 25.241%, and 16.8782% (% inhibition), 36.3655, 41.6775, 51.0757 (IC50). The optimum temperature for the number of BAL pickled bamboo shoots is 37°C, and the optimum temperature for the number of antioxidants is 15°C.